Therapeutic Potential of Berberine - Chen, Zihan (Transactions on Materials, Biotechnology and Life Sciences, 2024)
Berberine, an alkaloid extracted from plants, is used in the treatment of many diseases, has many pharmacological effects, and is accompanied by a high safety profile, which is popular in drug development and has been applied in many diseases. It shows significant effects on cancer, type 2 diabetes mellitus, gastrointestinal diseases, and cholesterol reduction as the inherent properties of berberine have inhibitory effects on these conditions, some by targeting specific steps in the disease progression, and others by acting directly on the pathogens themselves. Additionally, berberine also has several side effects, and patients should be cautious to avoid exceeding the recommended dosage. Also, it may interact with certain medications, presenting both benefits and risks. Therefore, it is important to take berberine under medical supervision and follow the doctor’s advice. This article summarizes several clinical trials, randomized controlled trials, and other experimental studies, including in vivo and in vitro experiments. During this review, it will focus on these four kinds of diseases, to explain the mechanism and description of the relationship between disease and berberine.